Performance analysis of CuInSe2 based solar cells using SCAPS-1D. (2022) - Moujoud, Salaheddine; Hartiti, Bouchaib; Touhtouh, Samira; Faddouli, Ali; Fadili, Salah; Stitou, Mohamed; Thevenin, Philippe; Hajjaji, Abdelowahed
Abstract: In this study we have simulated a CuInSe2 based solar cell. CuInSe2 solar cells belongs to the second generation of PV technology.The conventional structure of the cell Al/ZnO:Al/ZnO/CdS/CuInSe2 /Mo have been studied through. The simulation was performed by SCAPS-1D, one dimensional solar cell capacitance simulator, which is created by Marc Burglman from university of Gent in Belgium. Several effects like thickness, carrier density of CuInSe2 and gallium ratio were studied. The results of simulation showed that we have to control the thickness of absorber layer because going beyond 2 µm of thickness affect the performance of the cell especially fill factor that decreases even if the power conversion efficiency increases. The variation of carrier density showed that the optimum value is in the range of 10 16 cm −3 . This value should also be controlled to not have a degenerate compound. As for gallium content results showed that under a ratio of 0.33 we achieved an efficiency of 13.31%, which is due to the amelioration of absorption. Another effect has been evaluated is the effect of temperature, we varied temperature from 300°K to 400°K in order to see its influence. The results of varying temperature showed that all parameters decrease except the density of short circuit that increased. This study has helped us to understand the performance of CuInSe2 solar cell by knowing parameters that need to be controlled during production process.